(untitled) (Global Journal of Management and Business Research, 2020)
We are dealing with a psychological aspect of our actions and behavior and, consequently, we are focused on the Psychological approach of Marginalism. Starting with the German economist of the 19th century, Hermann Heinrich Gossen, with his Law of the Marginal Diminishing Returns, in fact his first law, passing through the analyses and approaches of this theoretical products, along with practical examples from around us, from media information, to reach the point in which to affirm that either in the diminishing returns, or increasing returns, it is a threshold above or beyond which the feeling of pleasure/fullness, even a state of happiness, tends to disappear.